Into the World of Underwater Swarm Robotics: Architecture, Communication, Applications and Challenges - Keerthi, Koyippilly S.; Mahapatra, Bandana; Menon, Varun Girijan (Recent Advances in Computer Science and Communications, 2020)
Background: With the curiosity of exploring the underwater world, science has devised various technologies and machines that can help them in performing activities like exploring, navigating and plunging into the unknown world of oceanography. Underwater Robot or vehicle can be claimed as an outcome of extensive research done by the scientists who aimed at discovering the unknown mysterious world of ocean and how it can benefit humanity. Swarm robotics is an entirely new section of robotics that has been developed based on swarm intelligence. Considering the fact, swarm robotics being still in nuptial stage, researchers have provided immense contribution with an aim to develop this technology. The objective of the paper is to present a comprehensive review covering the various technical and conceptual aspects of underwater swarm robotic system. Methods: A systematic review on state-of-the-art has been performed where contributions of various researchers was considered. The study emphasis on the concepts, technical background, architecture and communication medium along with its applicability in various fields that also include various issues and challenges faced while attaining them. Results: The incorporation of swarm intelligence in underwater robotics provides a new angle altogether into the working pattern of underwater robotic system. Conclusion: The article is a systematic presentation of swarm robot technologies, their mechanisms, conceived and designed communication medium with respect to adaptability of the vehicle to the versatile nature of water. The paper delineates the various conceptual and technical details and its beneficence to humanity.
Keywords: swarm robotics